Electric field modeling of outdoor insulator for optimized performance - Tali @ Razali, Mohd Hayumabdissalam (2014)
This project presents the study of electric field stress along the surface of a 132 kV ceramic post insulator. Insulators are among the important devices of the electric power transmission systems. They are used to support and separate conductors at high voltage. Different insulator shapes have been obtained by varying several parameters, which defines the shape of the post insulator .For each insulator shape, the maximum electric field stress occurring on the insulator surface has been determined under clean and dry environment. The COMSOL Multiphysics software has been employed to investigate the electric field stress along the insulator’s surface. The full detailed model of a dry and clean ceramic 132kV post insulator with 25 sheds has been developed for the base model calculation. The maximum value of electric field stress was found to be at the junction between the porcelain and the end fitting. End fittings with round edges tend to reduce the electric field stress along the insulator’s surface. With smaller first shed’s outer corner radius, the electric field stress slightly decreases. The electric field stress of the 25th shed near the top end fitting tends to reduce as the shed’s inclination angle is increased. Furthermore, as the shed’s diameter increases, the electric field stress increases except at the shed’s outer corner where the electric field stress decreases. With greater distance between the first shed and the bottom end fitting, the electric field stress becomes lower. The end fittings design was found to be significantly affecting the electric field stress along the surface of the post insulator. A modified post insulator is proposed and proven to have a better performance in term of electric field stress.